Experimental investigation of effect of roller burnishing process parameters on surface roughness and surface hardness of C40E steel. (2016) - Kumar, Naresh; Sachdeva, Anish; Singh, Lakhwinder Pal; Tripathi, Himanshu
Surface finish and dimensional accuracy are ever in demand because of strong influence of these characteristics on major functional properties like friction, fatigue strength, wear resistance, load carrying capacity, and corrosion resistance of any materials. In the present work the effect of burnishing process parameters like burnishing condition, burnishing speed, feed, depth of penetration, number of passes is investigated on the surface roughness and hardness of C40E steel. Taguchi design of experiment is used for present experimentation. Taguchi's L18 mixed orthogonal array is used for optimisation of input parameters and analysis of variance (ANOVA) is employed for concluding vital and fruitful results. Investigation reveals that minimum surface roughness value of .129 µm at wet burnishing condition .557 rpm speed, .06 mm/rev feed, 1.5 mm depth of penetration and double pass of tool and optimised surface hardness 94 HRB at dry burnishing condition, 371 rpm speed, 0.11 mm/rev feed, 1.5 mm depth of penetration and third pass of tool is obtained.